Limites do direito fundamental à liberdade religiosa no ambiente laboral - Guimarães, Sandrelly Monnique Silva (Universidade Federal Rural do Semi-Árido, 2017)
This work addresses the tensions and interactions in the workplace in relation to the religious freedom of employees and employers, reflecting the main principles governing the legal relationship of the employment contract and the fundamental right to exercise free expression of belief. To do so, we analyze elements that permeate this relationship, such as the directive power of the employer and free initiative in tension and conflicts with the rights of the employee's personality. The objective is to analyze the possibilities and limitations of the fundamental right to religious belief, considering the guiding principles of labor relations. The research carried out has a theoretical, bibliographical and documentary character, emphasizing the use of literature focused on the interactions between labor law and religion, using also the legislative exposition and judgments on the subject in question. In order to carry out this study, one begins with the reflections of authors such as Ingo Sarlet, Gilmar Mendes, Paulo Branco and Paulo Bonavides, and also Aloisio Cristovam dos Santos Junior. The study analyzed the fundamental right to religious freedom as one of the formators of the personality and dignity of the human person, hence the importance of protecting it from restrictions due to the employee's hyposufficient situation in the working relationship. It is concluded that the directive power of the employer and the principle of free initiative should not overlap with the right of personality of the employee and, more specifically, the employee's right to exercise their religious beliefs in the workplace, taking into consideration the Rights constitutionally Protected in relation to the dignity of the human person, as well as those referring to the social function of the company. It was also found that the jurisprudence considers possible the condemnation of the employer to repair the off-balance sheet damages caused by moral harassment of religious character, since it is an unconstitutional discriminatory practice.
Monografia
Keywords: Direito constitucional; Direito do trabalho; Religião; Liberdade religiosa; Constitutional law; Labor law; Religion; Freedom of religion; CIENCIAS SOCIAIS APLICADAS::DIREITO